2019
DOI: 10.1038/s41598-018-37147-9
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Activation of WR-2721 Mediates Radioprotection and Improved Survival from Lethal Fractionated Radiation

Abstract: Unresectable pancreatic cancer is almost universally lethal because chemotherapy and radiation cannot completely stop the growth of the cancer. The major problem with using radiation to approximate surgery in unresectable disease is that the radiation dose required to ablate pancreatic cancer exceeds the tolerance of the nearby duodenum. WR-2721, also known as amifostine, is a well-known radioprotector, but has significant clinical toxicities when given systemically. WR-2721 is a prodrug and is converted to it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…000664) were purchased from The Jackson Laboratory. Kras LSL/+ and Trp53 FL/FL ; Ptf1a Cre/+ animals were backcrossed to a pure C57BL/6 background as previously described (48).…”
Section: Methodsmentioning
confidence: 99%
“…000664) were purchased from The Jackson Laboratory. Kras LSL/+ and Trp53 FL/FL ; Ptf1a Cre/+ animals were backcrossed to a pure C57BL/6 background as previously described (48).…”
Section: Methodsmentioning
confidence: 99%
“…Undoubtedly, the most effective was WR-2721 or amifostine, a sulfhydryl prodrug activated by alkaline phosphatase to the active WR-1065. Salivary glands and the epithelial cells of intestine are highly enriched in this activating enzyme, and thus oral administration of WR-2721 just before radiation results in localized high production of the bioactive derivate, preventing radio-induced mucositis and GI damage without significant systemic side effects [ 86 , 87 , 88 , 89 ]. The underlying mechanisms of action are free radical scavenging and hydrogen atom donation, along with DNA protection and repair; all coupled to an initial induction of cellular hypoxia [ 90 , 91 , 92 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Afterwards, this study elucidated the correlation between miRNAs and the degree of radiation damage. They used the radioprotective agent amifostine, which is known to prolong survival in mice and humans by reducing radiation-related toxicity ( Pamujula et al, 2005 ; Molkentine et al, 2019 ; Singh and Seed, 2019 ), to inject mice intraperitoneally prior to irradiation. The results showed that all mice in the amifostine injection group (before IR) survived, and all the mentioned miRNAs above were significantly altered compared to the saline injection group (before IR), suggesting that this group of miRNAs was related to the ability to survive (or the degree of damage suffered) and not the radiation dose.…”
Section: Potential Of Mirnas As Biomarkers Of Exposure To Ionizing Ra...mentioning
confidence: 99%